Jirga and dispute resolution in Khyber Pakhtunkhwa: a critical analysis - Ahmad, Muhamad Hassan; Khan, Ihtesham Ullah; Eishan Jan, Mohammad Naqib (Serials Publications (P) Ltd., 2019)
Disputes are inevitable and take place in all human societies. Hence, the Pushtoon community is not immune from having disputes at all levels among individuals, families, tribes, or even nations. The Pushtoon community has been using the Jirga system which is the oldest and still one of the typical dispute resolution mechanisms in the society. Although the Jirga system has been very crucial in ensuring the administration of justice and harmony in the Pushtoon community in various ways, it has also been subjected to several criticisms due to its application of unwritten rules and informal structures which sometimes may lead to grave injustice to the parties to the disputes. Accordingly, this article aims at exploring the nature of the Jirga system being used in the Pushtoon community from Khyber Pakhtunkhwa; analysing the methods of dispute resolution through the Jirga system; and proposing viable recommendations for the betterment of the Jirga system in administration of justice in the said region.